On the mechanisms of superplasticity in Ti–6Al–4V. (15th February 2016) - Alabort, E.; Kontis, P.; Barba, D.; Dragnevski, K.; Reed, R.C.
Abstract: Surface observations are used to elucidate the deformation mechanisms responsible for the superplastic effect in Ti–6Al–4V. High-temperature in-situ tests for tensile and shear deformation modes are performed in the scanning electron microscope at temperatures in excess of 700 ∘ C. Grain boundary sliding is predominant; the micro-mechanics of accommodation are consistent with the dislocation-based Rachinger theory. The volume fraction of β plays a crucial role. For temperatures greater than 850 °C, the α grains remain unaffected; cavitation is minimal and slip bands needed for dislocation-based accommodation are detected in the β phase but are absent in α . At this temperature, grain neighbour switching is observed directly under shear deformation. At a temperature lower than 850 ∘ C, the β volume fraction is lower and a different mechanism is observed: slip bands in α and cavitation are found to accommodate grain boundary sliding. In addition, an increase in the α phase intragranular dislocation activity triggers the formation of subgrains and dynamic recrystallisation, consistent with the Rachinger dislocation creep effect. For temperatures lower than 700 ∘ C, superplasticity is absent; classical creep behaviour controlled by dislocation climb persists. A numerical treatment is presented which accounts for the Rachinger effect. The computational results are used to deconvolute the contributions of each of the competing mechanisms to the total strain accumulated. Graphical abstract: